Implementasi NLP Dalam Pembuatan Chatbot Customer Service Publisher Jurnal Studi Kasus LARISMA - Nasution, Mutiara Akbar; Fitri, Anisa; Rizwinie, Khesya Sabilah; Silaban, Vetryc Styphen; Khoirani, Fihi (Jurnal Sains, Teknologi & Komputer, 2024)
This research aims to develop a Customer Service Chatbot for Larisma Journal Publisher that can effectively answer questions and reduce response time to questions that are often similar. This research will design a Chatbot system that can facilitate users in interacting and finding information related to journal publishing, by applying Natural Language Processing. This chatbot system uses training data collected from various questions commonly asked by authors to produce accurate information, with data analysis methods involving preprocessing, training and model building. Testing the accuracy of this chatbot was carried out by the designer through a terminal in Google Colab by viewing and assessing the suitability between the questions and the answers generated. The test results state that this chatbot is able to provide effective responses by evaluating answers based on keywords in the chatbot, so as to provide the right answers.